Arene platform based hexa-amide receptors for anion recognition: single crystal X-ray structural and thermodynamic studies1. Issue 59 (28th June 2015) - Chakraborty, Sourav; Arunachalam, M.; Dutta, Ranjan; Ghosh, Pradyut
<x xml:space="preserve">Abstract</x> Compartmental recognition of [Cl2(inf>O/inf>O)2]2− in the cavity of p-fluoro-phenyl substituted hexa-amide receptor.